3-Hydroxy-3-phenylisoindolin-1-one 0.33-hydrate - Hong-Jun Zhu; Wen-Hong Zhang; Xiao-Li Zhang; Shan Liu (Acta Crystallographica Section E, 2009)
The asymmetric unit of the title compound, C14H11NO2·0.33H2O, contains three 3-hydroxy-3-phenylisoindolin-1-one (HPIO) molecules and one water molecule. The three independent HPIO molecules differ in the orientations of hydroxy and phenyl groups substituted at the 3-position with respect to the planar [r.m.s. deviations of 0.0173, 0.0170 and 0.0102 Å] dihydroisoindolin-1-one ring system. In the crystal structure, molecules are linked into a three-dimensional network by O—H...O, N—H...O and C—H...O hydrogen bonds.